The pervasive impact of global climate change on plant-nematode interaction continuum - Dutta, Tushar K.; Phani, Victor (Frontiers in Plant Science, 2023)
Pest profiles in today’s global food production system are continually affected by climate change and extreme weather. Under varying climatic conditions, plant-parasitic nematodes (PPNs) cause substantial economic damage to a wide variety of agricultural and horticultural commodities. In parallel, their herbivory also accredit to diverse ecosystem services such as nutrient cycling, allocation and turnover of plant biomass, shaping of vegetation community, and alteration of rhizospheric microorganism consortium by modifying the root exudation pattern. Thus PPNs, together with the vast majority of free-living nematodes, act as ecological drivers. Because of direct exposure to the open environment, PPN biology and physiology are largely governed by environmental factors including temperature, precipitation, humidity, atmospheric and soil carbon dioxide level, and weather extremes. The climate change driven atrocities such as global warming, elevated CO2, altered precipitation and the weather extremes including heat waves, droughts, floods, wildfires and storms greatly influence the biogeographic range, distribution, abundance, survival, fitness, reproduction, and parasitic potential of the PPNs. Changes in these biological and ecological parameters associated to the PPNs exert huge impact on agriculture. Yet, depending on how adaptable the species are according to their geo-spatial distribution, the consequences of climate change include both positive and negative effects on the PPN communities. While assorting the effects of climate change as a whole, it can be estimated that the changing environmental factors, on one hand, will aggravate the PPN damage by aiding to abundance, distribution, reproduction, generation, plant growth and reduced plant defense, but the phenomena like sex reversal, entering cryptobiosis, and reduced survival should act in counter direction. This seemingly creates a contraposition effect, where assessing any confluent trend is difficult. However, as the climate change effects will differ according to space and time it is apprehensible that the PPNs will react and adapt according to their location and species specificity.Integrated nematode management involving precise monitoring and modeling-based studies of population dynamics in relation to climatic fluctuations with escalated reliance on biocontrol, host resistance, and other safer approaches like crop rotation, crop scheduling, cover cropping, biofumigation, use of FYM would surely prove to be viable options.